What happens inside a moist chamber culture? - Rojas Alvarado, Carlos Alonso (2025)
An entire subset of moist chamber cultures was used to document both the internal temperature and the moistness of the filter paper surface. These metrics are presented and studied in the context of both the temperature and the humidity of the room where the experiment was conducted. Overall, it seems that internal and external temperatures are independent, but internal and external measurements of air humidity and surface moistness seem to be related. The data presented erein are meant to generate only a discussion, but should be supported more robustly by experiments dedicated to studying the limitations of the moist chamber technique culture in the future.